KNOWLEDGE, ATTITUDE AND PRACTICE OF HEALTHCARE WORKERS TOWARDS NOVEL CORONA VIRUS (COVID-19) IN JUGAL HOSPITAL, HARARI REGIONAL STATE, ETHIOPIA - Jamie, Arif Hussen (Public Health of Indonesia, 2020)
Introduction: Coronavirus (CoVs) belong to the subfamily Corona virinae in the family of Corona viridae of the order Nido virales, and this sub family includes four genera: Alpha corona virus, Beta corona virus, Gamma corona virus and Delta corona virus. The genome of CoVs is a single"stranded positive"sense RNA (+ssRNA) (~30 kb) with 5"²"cap structure and 3"²"poly"A tail.Method:  Cross sectional quantitative study was conducted from February to March 2020 at Jugal Hospital, Harar, Ethiopia, which is found 525 km to East of Addis Ababa. Data were collected using a self-administered questionnaire. Data were analyzed using a descriptive statistic using SPSS version 20.Result: Majority of the staffs had a good knowledge about COVID-19, almost all 201(97.10%) answered they are not ready to give care for a patient who is positive for COVID-19 and only 7(3.38%) of the participants answered that there is enough soap and water to wash hand, hand sanitizers and personal protective equipment materials.Conclusion: The findings of this study showed that majority of the respondents have adequate knowledge, attitude and practice about COVID-19. Nevertheless, greater than 95% of respondents said that they are not ready to give care for a patient who is positive for COVID-19, there is no enough soap and water to wash hand, hand sanitizers and Personal Protective Equipment materials like mask, glove and they are afraid that one of their family members can get infection.